Pre-gestational diabetes and pregnancy - Oats, Jeremy J. N. (Henry Stewart Talks, 2014)
Pregestational and gestational diabetes mellitus (DM), Diabetes in pregnancy: historical perspective, Perinatal mortality and morbidity, Offspring’s complications, Prenatal spontaneous abortions, Prenatal congenital malformations, Relationship to glycaemic control, Haemoglobin A1c: abortions & malformations, Caudal regression syndrome in DM, Prenatal macrosomia, Perinatal birth hypoxia, Perinatal birth trauma, Shoulder dystocia, Perinatal Caesarean section, Neonatal respiratory distress, Neonatal hypoglycaemia, Neonatal cardiac complications, Type 1 vs. type 2 DM, Congenital malformations, Effect of obesity, Late fetal death, Management of diabetic pregnancies, Medical management, Oral hypoglycaemics, Fetoplacental surveillance, Timing of delivery, Management of neonate of diabetic mother